Gamification Learning Framework for Improving Students' Learning Motivation - Yurissa, Putri Norma; La Kamadi; Haeruddin, Sofyan (Education and Talent Development Center Indonesia (ETDC Indonesia), 2022)
The Covid-19 pandemic necessitates full virtual or online learning by educational entities. Students' excitement for studying decreases throughout online learning, making them appear inactive during the learning process. The goal of this study is to see if using gamification in virtual learning may boost students' enthusiasm to learn. This type of study employs classroom action research with a total of 93 students from class IV at MIN 3 Jombang in the odd semester of the 2021/2021 academic year. Questionnaires and observations were employed to obtain data. A questionnaire was employed to conduct this study. Descriptive quantitative data analysis was utilized to analyze the data. The percentage of typical class students' learning motivation increased from 77.84 percent in the first cycle to 90.32 percent in the second cycle, meeting the study's 80 percent success threshold. According to the findings, the use of gamification in learning could improve the learning motivation of fourth-grade students at MIN 3 Jombang.